Privacy in public spaces: what expectations of privacy do we have in social media intelligence? - Edwards, Lilian; Urquhart, Lachlan (Oxford University Press, 2016)
In this paper we give an introduction to the transition in contemporary surveillance from top down traditional police surveillance to profiling and “pre-crime” methods. We then review in more detail the rise of open source (OSINT) and social media (SOCMINT) intelligence and its use by law enforcement and security authorities. Following this we consider what if any privacy protection is currently given in UK law to SOCMINT. Given the largely negative response to the above question, we analyse what reasonable expectations of privacy there may be for users of public social media, with reference to existing case law on art 8 of the ECHR. Two factors are in particular argued to be supportive of a reasonable expectation of privacy in open public social media communications: first, the failure of many social network users to perceive the environment where they communicate as “public”; and secondly, the impact of search engines (and other automated analytics) on traditional conceptions of structured dossiers as most problematic for state surveillance. Lastly, we conclude that existing law does not provide adequate protection for open SOCMINT and that this will be increasingly significant as more and more personal data is disclosed and collected in public without well-defined expectations of privacy.